2006
DOI: 10.1002/jbt.20104
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin resistance in a French strain of rats

Abstract: A warfarin-resistant strain and a warfarin-susceptible strain of wild rats (Rattus norvegicus) maintained in enclosures of the National Veterinary School of Lyon (France) were studied to determine the mechanism of the resistance to anticoagulant rodenticides. A low vitamin K epoxide reductase (VKOR) activity has been reported for many resistant rat strains. As recently suggested, mutations in the vitamin K epoxide reductase subunit 1 (VKORC1) gene are the genetic basis of anticoagulant resistance in wild popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
68
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 24 publications
10
68
1
Order By: Relevance
“…Resistance factors corresponding to the ratio between K i obtained for the mutated VKORC1 and for the wild‐type VKORC1 were determined for each VKORC1 protein toward each anticoagulant rodenticide. These in vitro resistance factors used for the first time to study the consequences of the Vkorc1 mutations in brown rats (Hodroge et al., 2011) were shown to be totally coherent with resistance factors obtained using liver microsomes (Lasseur et al., 2005) and with resistance factors obtained by BCR tests after peros administration of AVK to strains of rats homozygous for wild‐type Vkorc1 or Vkorc1‐Y139F (Grandemange et al., 2009) or by feeding tests in mice homozygous for wild‐type Vkorc1 or Vkorc1 spr (Goulois et al., 2017). Therefore, in this study, the resistance factors determined in vitro using recombinant VKORC1 expressed in yeast are considered as good markers of the in vivo resistance phenotype of rodents, for whom we possessed only fragments of tail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance factors corresponding to the ratio between K i obtained for the mutated VKORC1 and for the wild‐type VKORC1 were determined for each VKORC1 protein toward each anticoagulant rodenticide. These in vitro resistance factors used for the first time to study the consequences of the Vkorc1 mutations in brown rats (Hodroge et al., 2011) were shown to be totally coherent with resistance factors obtained using liver microsomes (Lasseur et al., 2005) and with resistance factors obtained by BCR tests after peros administration of AVK to strains of rats homozygous for wild‐type Vkorc1 or Vkorc1‐Y139F (Grandemange et al., 2009) or by feeding tests in mice homozygous for wild‐type Vkorc1 or Vkorc1 spr (Goulois et al., 2017). Therefore, in this study, the resistance factors determined in vitro using recombinant VKORC1 expressed in yeast are considered as good markers of the in vivo resistance phenotype of rodents, for whom we possessed only fragments of tail.…”
Section: Discussionmentioning
confidence: 99%
“…During pest control management with one of these molecules, only the brown rats carrier for one of these mutations, in the homozygous state and also, but to a lesser extent, in the heterozygous state, survive. Nevertheless, brown rats carriers of one of these mutations are still susceptible to AVK such as difethialone, brodifacoum, and flocoumafen and control with one of these molecules is still possible (Hodroge et al., 2011; Lasseur et al., 2005). …”
Section: Discussionmentioning
confidence: 99%
“…Resistance to warfarin in wild rodents was first observed in Scotland in 1958 (Boyle, 1960). Since then, resistance mechanisms have been intensely studied in rats, and recent research has shown that warfarin resistance can be explained by VKOR mutation and/or elevated warfarin metabolic activity (Lasseur et al, 2005;Ishizuka et al, 2007). These reports suggested the VKOR inhibition rate by warfarin and the metabolic activity of warfarin were important parameters leading to the development of sensitivity against warfarin.…”
Section: Introductionmentioning
confidence: 99%
“…This reaction is catalyzed by the vitamin K epoxide reductase (VKOR) activity. This activity is inhibited in a noncompetitive manner by vitamin K antagonists (VKAs) (11) (Fig. 1).…”
mentioning
confidence: 99%